"She loves books & ideas, & strides along low shoes like englishwoman": British models and graduates from Anglican girls' secondary schools in Palestine, 1918-48 - Okkenhaug, Inger Marie (Islam and Christian-Muslim relations, 2002)
During the mandate period of British rule in Palestine, urban middle- and upper-class Arab women challenged the traditions that had secluded them from public life. The influence of missionary secondary education was the first and crucial step to the changing social roles of these women. Despite the general historical interpretation that Western missionary education merely modernized the domestic dimension of the indigenous women's identity, the Anglican mission schools in Palestine provided women with a liberal education in addition to offering a professional life and gainful employment as a legitimate option for young women. This paper calls for further research to be done on the topic.